Preparation method of high-performance Cu-Be-Co alloy strip

By controlling the Be and Co content in Cu-Be-Co alloy and performing cold deformation treatment after aging, the BeCo phase is formed, the problem of insufficient mechanical properties and conductive properties of low beryllium copper alloy is solved, and high tensile strength is achieved , excellent stress relaxation resistance and high conductivity comprehensive performance improvement.

CN119464790APending Publication Date: 2025-02-18INSTITUTE OF MATERIALS & INTELLIGENT MANUFACTURING JIANGXI ACADEMY OF SCIENCES +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411585134.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing low beryllium copper alloys have shortcomings in mechanical properties and electrical conductivity, and it is difficult to meet the requirements of high conductivity, high strength and excellent stress relaxation resistance in current-carrying occasions.

Method used

By controlling the Be and Co content in the Cu-Be-Co alloy and performing cold deformation treatment after aging, a small and diffuse distribution of BeCo phase is formed, thereby improving the mechanical properties of the alloy while maintaining high conductivity.

Benefits of technology

The Cu-Be-Co alloy strip has high tensile strength, excellent stress relaxation resistance and high conductivity, which meets the performance requirements in current-carrying occasions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119464790A_ABST
    Figure CN119464790A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a high-performance Cu-Be-Co alloy strip. The preparation method comprises the following steps: preparing raw materials according to alloy components and contents of 0.2-0.4 wt% of Be, 0.5-0.6 wt% of Co and the balance of Cu; the preparation method comprises the following steps: smelting an alloy ingot by adopting a vacuum induction electromagnetic suspension furnace; on the basis of traditional solid solution-deformation-aging, the content of Be and Co in the Cu-Be-Co alloy is controlled, and cold deformation treatment is added after aging. According to the method, the mechanical property of the Cu-Be-Co alloy is greatly enhanced while the high conductivity is guaranteed, the Cu-Be-Co alloy strip with excellent comprehensive performance is obtained, the tensile strength of the obtained alloy strip reaches 863 Mpa, the conductivity is about 49.9% IACS, and the stress relaxation resistance performance that the stress relaxation is smaller than 10% within 100 h at the room temperature is achieved. The method is relatively simple, easy to operate and low in cost, and can meet the performance requirements of the copper alloy for contact current carrying.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of materials, and relates to a Cu-Be-Co alloy strip with high strength, high conductivity and excellent stress relaxation resistance and a preparation technology thereof. Background Art

[0002] Beryllium copper alloy is a copper alloy with excellent comprehensive performance. Due to the reliability and excellent performance of beryllium copper alloy, it is widely used in heat dissipation and current carrying occasions such as electrical contact components for aerospace, radar systems, and battery terminals for electronic communication products. At present, high-beryllium copper alloys are more commercially used. Although high-beryllium copper alloys have excellent mechanical properties, they will bring many difficulties to processing and production, and their electrical conductivity is not ideal (conductivity <30% IACS). In addition, the toxicity of beryllium is also an issue that cannot be ignored for practical applications. Therefore, reducing the beryllium content is the future development trend of beryllium copper alloys.

[0003] The electrical and thermal conductivity of low-beryllium-content beryllium copper alloys (Be content: 0.2%~0.6%) are improved due to the reduction of beryllium content, but the mechanical properties are significantly reduced. The low-beryllium beryllium copper alloys reported so far often have high electrical conductivity, but unsatisfactory mechanical properties. Commercial current-carrying occasions usually require service materials to have high electrical conductivity, high strength, and excellent stress relaxation resistance. Therefore, the study of low-beryllium beryllium copper alloys with high strength, high conductivity, and excellent stress relaxation resistance and their preparation methods is crucial for their practical applications. Summary of the invention

[0004] The purpose of the present invention is to provide a Cu-Be-Co alloy strip with excellent comprehensive performance and a preparation method in order to further improve the mechanical properties and electrical conductivity of low-beryllium copper alloy strip for contact current carrying. The preparation technology provided by the present invention is relatively simple, easy to operate and low-cost, and the prepared Cu-Be-Co alloy strip has high tensile strength, high electrical conductivity and excellent stress relaxation resistance.

[0005] The high-performance Cu-Be-Co alloy strip of the present invention has the following composition and percentage content: Be is 0.2-0.4 wt%, Co is 0.5-0.6 wt%, and the rest is Cu.

[0006] The method for preparing a high-performance Cu-Be-Co alloy strip described in the present invention comprises the following steps.

[0007] (1) Melting of alloy ingot: 99.9% high-purity copper, high-purity beryllium and high-purity cobalt are selected as raw materials. According to the alloy composition and mass percentage, Be is 0.2~0.4 wt%, Co is 0.5~0.6 wt%, and the rest is Cu. A vacuum induction electromagnetic suspension furnace is used for melting. The induction heating device of the vacuum induction furnace is turned on to completely melt the raw materials in the heating coil into a molten state, and then the Cu-Be-Co alloy melt is cast into a mold. After cooling in the furnace, the ingot is taken out, that is, the Cu-Be-Co alloy ingot.

[0008] (2) Preparation of alloy strips: First, the Cu-Be-Co alloy ingot was cut into plate-shaped specimens with a thickness of 4 mm using a wire cutting machine. The specimens were subjected to a solution heat treatment at 930 ℃~970 ℃ for 1 h in a resistance box furnace. After the insulation time was over, the specimens were immediately taken out and water-cooled to room temperature. The surface of the solid solution alloy was polished with sandpaper. Then, at room temperature and a roll speed of 30 rpm, the specimens were pressed down by 10% at a time until the specimen thickness reached 0.8~1.0 mm, i.e., the total deformation was 70~80%. The specimens in this state were recorded as cold rolled 1. Then, the cold rolled 1 specimens were subjected to aging heat annealing at 450 ℃ for 20 min~4 h. After aging, the specimens were taken out and air-cooled to room temperature. Subsequently, the aged sample was again rolled down by 10% at room temperature and 30 rpm until the sample thickness reached 0.4-0.5 mm, i.e., the total deformation was 50%, and the final Cu-Be-Co alloy strip was obtained, which was recorded as cold rolling 2.

[0009] Preferably, the temperature of the solution heat treatment of the Cu-Be-Co alloy plate in step (2) is 950°C and the insulation time is 1 hour; the deformation amount of the cold rolling treatment of the solid solution alloy is 75%; the temperature of the aging treatment of the cold rolled alloy strip is 450°C and the time is 20 min~4 h.

[0010] (3) Testing, analysis and characterization: The microstructure, mechanical properties and conductive properties of the prepared Cu-Be-Co alloy strip are tested, analyzed and characterized.

[0011] The principles and advantages of the present invention are described in detail as follows: The present invention explores a simple process flow for Cu-Be-Co low-beryllium copper alloy strips, controls the content of Be and Co elements in the Cu-Be-Co alloy, and adds cold deformation treatment after aging, with the aim of greatly enhancing the mechanical properties of the low-beryllium copper alloy through deformation strengthening and synergistic precipitation. By adjusting the aging parameters and the amount of cold rolling deformation, fine and dispersed BeCo phases are fully precipitated in the alloy strip, further optimizing the mechanical properties of the Cu-Be-Co alloy while ensuring high electrical conductivity.

[0012] The Cu-Be-Co alloy strip provided by the present invention is based on the traditional "solid solution-deformation-aging", by controlling the content of Be and Co elements in the Cu-Be-Co alloy, and adding cold deformation treatment after aging, while ensuring high conductivity, the mechanical properties of the Cu-Be-Co alloy are greatly enhanced, and a Cu-Be-Co alloy strip with excellent comprehensive performance is obtained. The tensile strength of the obtained alloy strip reaches 863Mpa, while the conductivity is about 49.9%IACS, and the stress relaxation resistance of 100h stress relaxation at room temperature is less than 10%. The preparation technology provided by the present invention is relatively simple, easy to operate and low-cost, and greatly meets the performance requirements of copper alloys for contact current carrying. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 This is the metallographic structure diagram of Cu-Be-Co cast alloy.

[0014] Figure 2 Hardness change of Cu-Be-Co alloy strip during aging annealing.

[0015] Figure 3 The electrical conductivity of Cu-Be-Co alloy strip changes during aging annealing.

[0016] Figure 4 Mechanical properties of Cu-Be-Co alloy after different process treatments.

[0017] Figure 5 Stress relaxation resistance of Cu-Be-Co cast alloy and final alloy strip. DETAILED DESCRIPTION

[0018] The present invention is further described in detail below in conjunction with specific implementation cases. It is pointed out that the following implementation cases are only used to illustrate the specific implementation methods of the present invention and cannot limit the scope of protection of the present invention. Example 1

[0019] The Cu-Be-Co alloy provided in this embodiment has an alloy composition and a mass percentage of 0.3wt% Be, 0.5wt% Co, and the rest is Cu configured raw materials, and the raw material purity is 99.9%. A vacuum induction electromagnetic suspension furnace is used for smelting, and the induction heating device of the vacuum induction furnace is turned on to completely melt the raw materials in the heating coil to a molten state, and then the Cu-Be-Co alloy melt is cast into a mold, and the ingot is taken out after cooling with the furnace, that is, the Cu-Be-Co alloy ingot. The wire cutting machine cuts the Cu-Be-Co alloy ingot into several plate-shaped samples with a thickness of 4 mm, and performs a solid solution heat treatment at 930 ° C and 1h in a resistance box furnace. After the insulation time is over, the sample is immediately taken out and water-cooled to room temperature. The surface of the solid solution alloy is polished with sandpaper, and then pressed down by 10% at room temperature and a roller speed of 30 rpm until the sample thickness reaches 0.8mm, that is, the total deformation is 80%, and the sample is recorded as cold rolling 1 in this state. Then, the cold-rolled sample was subjected to aging heat annealing at 450°C for 20 min. After aging, the sample was taken out and air-cooled to room temperature, thereby obtaining the finished product of Example 1. Example 2

[0020] The Cu-Be-Co alloy provided in this embodiment has an alloy composition and a mass percentage of 0.3wt% Be, 0.5wt% Co, and the rest is Cu configured raw materials, and the raw material purity is 99.9%. A vacuum induction electromagnetic suspension furnace is used for smelting, and the induction heating device of the vacuum induction furnace is turned on to completely melt the raw materials in the heating coil to a molten state, and then the Cu-Be-Co alloy melt is cast into a mold, and the ingot is taken out after cooling with the furnace, that is, the Cu-Be-Co alloy ingot. The wire cutting machine cuts the Cu-Be-Co alloy ingot into several plate-shaped samples with a thickness of 4 mm, and performs a solid solution heat treatment at 930 ° C and 1h in a resistance box furnace. After the insulation time is over, the sample is immediately taken out and water-cooled to room temperature. The surface of the solid solution alloy is polished with sandpaper, and then pressed down by 10% at room temperature and a roller speed of 30 rpm until the sample thickness reaches 0.8mm, that is, the total deformation is 80%, and the sample is recorded as cold rolling 1 in this state. Then, the cold-rolled sample was subjected to aging heat annealing at 450°C for 40 min. After aging, the sample was taken out and air-cooled to room temperature to obtain the finished product of Example 2. Example 3

[0021] The Cu-Be-Co alloy provided in this embodiment has an alloy composition and a mass percentage of 0.3wt% Be, 0.5wt% Co, and the rest is Cu configured raw materials, and the raw material purity is 99.9%. A vacuum induction electromagnetic suspension furnace is used for smelting, and the induction heating device of the vacuum induction furnace is turned on to completely melt the raw materials in the heating coil to a molten state, and then the Cu-Be-Co alloy melt is cast into a mold, and the ingot is taken out after cooling with the furnace, that is, the Cu-Be-Co alloy ingot. The wire cutting machine cuts the Cu-Be-Co alloy ingot into several plate-shaped samples with a thickness of 4 mm, and performs a solid solution heat treatment at 970 ° C and 1h in a resistance box furnace. After the insulation time is over, the sample is immediately taken out and water-cooled to room temperature. The surface of the solid solution alloy is polished with sandpaper, and then pressed down by 10% at room temperature and a roller speed of 30 rpm until the sample thickness reaches 1mm, that is, the total deformation is 70%, and the sample is recorded as cold rolling 1 in this state. Then, the cold-rolled sample was subjected to aging heat annealing at 450°C for 60 min. After aging, the sample was taken out and air-cooled to room temperature, thereby obtaining the finished product of Example 3. Example 4

[0022] The Cu-Be-Co alloy provided in this embodiment has an alloy composition and a mass percentage of 0.3wt% Be, 0.5wt% Co, and the rest is Cu configured raw materials, and the raw material purity is 99.9%. A vacuum induction electromagnetic suspension furnace is used for smelting, and the induction heating device of the vacuum induction furnace is turned on to completely melt the raw materials in the heating coil to a molten state, and then the Cu-Be-Co alloy melt is cast into a mold, and the ingot is taken out after cooling with the furnace, that is, the Cu-Be-Co alloy ingot. The wire cutting machine cuts the Cu-Be-Co alloy ingot into several plate-shaped samples with a thickness of 4 mm, and performs a solid solution heat treatment at 970 ° C and 1h in a resistance box furnace. After the insulation time is over, the sample is immediately taken out and water-cooled to room temperature. The surface of the solid solution alloy is polished with sandpaper, and then pressed down by 10% at room temperature and a roller speed of 30 rpm until the sample thickness reaches 1mm, that is, the total deformation is 70%, and the sample is recorded as cold rolling 1 in this state. Then, the cold-rolled sample was subjected to aging heat annealing at 450° C. for 2 h. After aging, the sample was taken out and air-cooled to room temperature, thereby obtaining the finished product of Example 4. Example 5

[0023] The Cu-Be-Co alloy provided in this embodiment has an alloy composition and a mass percentage of 0.3wt% Be, 0.5wt% Co, and the rest is Cu configured raw materials, and the raw material purity is 99.9%. A vacuum induction electromagnetic suspension furnace is used for smelting, and the induction heating device of the vacuum induction furnace is turned on to completely melt the raw materials in the heating coil to a molten state, and then the Cu-Be-Co alloy melt is cast into a mold, and the ingot is taken out after cooling with the furnace, that is, the Cu-Be-Co alloy ingot. The wire cutting machine cuts the Cu-Be-Co alloy ingot into several plate-shaped samples with a thickness of 4 mm, and performs a solid solution heat treatment at 950 ° C and 1h in a resistance box furnace. After the insulation time is over, the sample is immediately taken out and water-cooled to room temperature. The surface of the solid solution alloy is polished with sandpaper, and then pressed down by 10% at room temperature and a roller speed of 30 rpm until the sample thickness reaches 0.9mm, that is, the total deformation is 75%. The sample is recorded as cold rolling 1 in this state. Then, the cold-rolled sample was subjected to aging heat annealing at 450° C. for 3 h. After aging, the sample was taken out and air-cooled to room temperature, thereby obtaining the finished product of Example 5. Example 6

[0024] The Cu-Be-Co alloy provided in this embodiment has an alloy composition and a mass percentage of 0.3wt% Be, 0.5wt% Co, and the rest is Cu configured raw materials, and the raw material purity is 99.9%. A vacuum induction electromagnetic suspension furnace is used for smelting, and the induction heating device of the vacuum induction furnace is turned on to completely melt the raw materials in the heating coil to a molten state, and then the Cu-Be-Co alloy melt is cast into a mold, and the ingot is taken out after cooling with the furnace, that is, the Cu-Be-Co alloy ingot. The wire cutting machine cuts the Cu-Be-Co alloy ingot into several plate-shaped samples with a thickness of 4 mm, and performs a solid solution heat treatment at 950 ° C and 1h in a resistance box furnace. After the insulation time is over, the sample is immediately taken out and water-cooled to room temperature. The surface of the solid solution alloy is polished with sandpaper, and then pressed down by 10% at room temperature and a roller speed of 30 rpm until the sample thickness reaches 0.9mm, that is, the total deformation is 75%. The sample is recorded as cold rolling 1 in this state. Then, the cold-rolled sample was subjected to aging heat annealing at 450° C. for 4 h. After aging, the sample was taken out and air-cooled to room temperature, thereby obtaining the finished product of Example 6. Example 7

[0025] The Cu-Be-Co alloy provided in this embodiment has an alloy composition and a mass percentage of 0.3wt% Be, 0.5wt% Co, and the rest is Cu configured raw materials, and the raw material purity is 99.9%. A vacuum induction electromagnetic suspension furnace is used for smelting, and the induction heating device of the vacuum induction furnace is turned on to completely melt the raw materials in the heating coil to a molten state, and then the Cu-Be-Co alloy melt is cast into a mold, and the ingot is taken out after cooling with the furnace, that is, the Cu-Be-Co alloy ingot. The wire cutting machine cuts the Cu-Be-Co alloy ingot into several plate-shaped samples with a thickness of 4 mm, and performs a solid solution heat treatment at 960 ° C and 1h in a resistance box furnace. After the insulation time is over, the sample is immediately taken out and water-cooled to room temperature. The surface of the solid solution alloy is polished with sandpaper, and then pressed down by 10% at room temperature and a roller speed of 30 rpm until the sample thickness reaches 1mm, that is, the total deformation is 75%, and the sample is recorded as cold rolling 1 in this state. Then, the cold-rolled sample was subjected to aging heat annealing at 450°C for 60 min, and after aging, the sample was taken out and air-cooled to room temperature, thus obtaining the finished product of Example 3. Subsequently, the aged sample was again rolled down by 10% at room temperature and 30 rpm until the sample thickness reached 0.4 mm, i.e., the total deformation was 50%, and the final alloy was recorded as cold-rolled 2, i.e., the finished product of Example 7 was obtained.

[0026] The hardness and electrical conductivity of the Cu-Be-Co alloy strips prepared in Examples 1 to 6 are shown in Figures 2 and 3 .

[0027] The mechanical properties of the Cu-Be-Co alloy strip prepared in Example 7 at each process stage are as follows: Figure 4 The results show that the cold rolling process after annealing can significantly improve the yield strength and tensile strength of the strip, but the electrical conductivity decreases to about 49.9 IACS.

[0028] Figure 5 The stress relaxation resistance of Cu-Be-Co alloy strip in the cast state and the final state after re-rolling. Figure 4 The data results show that the process implemented by the present invention can greatly improve the stress relaxation resistance of the Cu-Be-Co alloy, and the strip finally obtained has high strength, high electrical conductivity and excellent stress relaxation resistance.

Claims

1. A method for preparing a high-performance Cu-Be-Co alloy strip, characterized in that The steps include: (1) Melting of alloy ingot: 99.9% high-purity copper, high-purity beryllium and high-purity cobalt are selected as raw materials, and the alloy composition and mass percentage are as follows: Be is 0.2-0.4 wt%, Co is 0.5-0.6 wt%, and the rest is Cu. A vacuum induction electromagnetic suspension furnace is used for melting. The induction heating device of the vacuum induction furnace is turned on to completely melt the raw materials in the heating coil into a molten state, and then the Cu-Be-Co alloy melt is cast into a mold. After cooling in the furnace, the ingot is taken out, i.e., a Cu-Be-Co alloy ingot. (2) Preparation of alloy strips: First, the Cu-Be-Co alloy ingot was cut into plate-shaped specimens with a thickness of 4 mm using a wire cutting machine. The specimens were solution treated at 930°C~970°C for 1 h in a resistance box furnace. After the insulation time was over, the specimens were immediately taken out and water-cooled to room temperature. The surface of the solid solution alloy was polished with sandpaper. Then, the specimens were rolled down by 10% at room temperature and a roller speed of 30 rpm until the specimen thickness reached 0.8~1.0 mm. The total deformation was 70~80%. The specimens in this state were recorded as cold rolled 1. Then, the cold rolled 1 specimens were subjected to aging heat annealing at 450°C for 20 min~4 h. After aging, the specimens were taken out and air-cooled to room temperature. Then, the aged specimens were rolled down by 10% at room temperature and a roller speed of 30 rpm until the specimen thickness reached 0.4~0.5 mm, the total deformation amount is 50%, and the final Cu-Be-Co alloy strip is obtained, which is recorded as cold rolling 2; (3) Testing, analysis and characterization: The microstructure, mechanical properties and conductive properties of the prepared Cu-Be-Co alloy strip are tested, analyzed and characterized.

2. The method for preparing a high-performance Cu-Be-Co alloy strip according to claim 1, characterized in that The temperature of the solution heat treatment of the Cu-Be-Co alloy plate in step (2) is 950° C. and the heat preservation period is 1 hour.

3. The method for preparing a high-performance Cu-Be-Co alloy strip according to claim 1, characterized in that The deformation amount of the cold rolling treatment of the solid solution alloy in step (2) is 75%.

4. The method for preparing a high-performance Cu-Be-Co alloy strip according to claim 1, characterized in that In step (2), the temperature for aging treatment of the cold-rolled alloy strip is 450° C. and the time is 20 min to 4 h.

Citation Information

Cited By

  • Regulation and control method for synergistically improving strong-electrical property of elastic copper alloy

    CN121610666A